Nutritional and Compositional Changes in α-tomatine Rich Ready-To-Serve Beverage From Matured Green Tomato (Solanium Lycopersium) - Vithal Balavant Kudachikar; P Geethanjali; Prakash Om; Kumar Amarjeet; Athar Singh Chauhan (Indonesian Food and Nutrition Progress, 2021)
The study aimed to develop and evaluate the storage stability of α-Tomatine rich ready-to-serve (RTS) beverages from green tomato juice at low temperature (LT, 4±1 °C) up to 90 days. The results indicated the α-tomatine content in green tomato juice and in RTS beverage was found to be 43.23±3.59 mg/100 mL and 3.94±0.21 mg/100 mL respectively. The stability of the product stored in a Brown glass bottle (BB) container was excellent with better retention of α-Tomatine (2.31±0.29 mg/100 mL), total phenolic content (1.42 mg GAE/100 mL), ascorbic acid (17.66 mg/100 mL), total chlorophyll (1.07 mg/100mL) and viscosity (15.46 cp), with high sensory scores (7.6) as compared to the quality of the product (with 6.8 sensory scores)stored in a white glass bottle (WB) container. The microbial counts of products stored in both containers after 90 days indicated within the permissible limit.